"It's Not You, It's Me": Examining the Roles of Romantic Self-Blame and Social Support in Pathways From Peer Victimization to Emerging Adult Depressive Symptoms - Schacter, Hannah L. (Journal of interpersonal violence, 2022)
Although experiences of adolescent peer victimization elevate risk for depressive symptoms during emerging adulthood, the mechanisms underlying this pathway are not well-understood. Drawing from attribution theory and models of relational schemas, the current study introduces romantic self-blame as a putative novel mechanism linking adolescent peer victimization to emerging adult depressive symptoms and evaluates perceived social support as a protective factor. A diverse sample of 350 emerging adults completed self-report measures of retrospective peer victimization, romantic characterological and behavioral self-blaming attributions, social support, and depressive symptoms. Confirmatory factor analyses supported the hypothesized two-factor structure of romantic self-blame. Additionally, conditional process models demonstrated that elevated romantic characterological?but not behavioral?self-blame partially explained the association between retrospective peer victimization and current depressive symptoms, particularly among those perceiving low social support. Results suggest that earlier peer victimization may alter emerging adults? romantic appraisals in ways that increase distress, particularly in the absence of supportive interpersonal relationships.